Bio-templated silica composites for next-generation biomedical applications - Albert, Karunya; Huang, Xin-Chun; Hsu, Hsin-Yun (My University, 2017)
Silica-based materials have extensive biomedical applications owing to their unique physical, chemical, and biological properties. Recently, increasing studies have examined the mechanisms involved in biosilicification to develop novel, fine-tunable, eco-friendly materials and/or technologies. In this review, we focus on recent developments in bio-templated silica synthesis and relevant applications in drug delivery systems, tissue engineering, and biosensing.
Keywords: Silica; Composite; Nanoparticle; Biomolecular template; Biosilica